10-Gingerol as an inducer of apoptosis through HTR1A in cumulus cells: In-vitro and in-silico studies. Issue 5 (October 2017) - Kiptiyah, Kiptiyah; Widodo, Widodo; Ciptadi, Gatot; Aulanni'am, Aulanni'am; Widodo, Mohammad A.; Sumitro, Sutiman B.
الملخص: أهداف البحث: تلعب الخلايا المحيطة بالبويضة دورا حاسما كوسيط أساسي في نضج البويضات. ويحتوي الزنجبيل على ١٠-جينجيرول، الذي يمكن أن يحفز موت الخلايا المبرمج في خلايا سرطان القولون. واستنادا إلى هذه الفرضية، هدفت هذه الدراسة إلى تحديد ما إذا كان ١٠ جينجيرول قادرا على تحريض موت الخلايا المبرمج في خلايا طبيعية، وتحديدا الخلايا المحيطة بالبويضة. طرق البحث: استخدمت هذه الدراسة التحليل المختبري للخلايا المحيطة بالبويضة المستزرعة في محلول م ١٩٩ والمحتوي على١٠ جينجيرول في تركيزات مختلفة (١٢، ١٦، و٢٠ ميكرومول) ومن ثم الكشف عن نشاط قاتل للخلايا مبكر باستخدام عدة أنيكسين - فلورسين أيسو ثايو سايانيت للكشف. النتائج: تُظهر البيانات في التجارب المختبرية أن عدد خلايا الموت المبرمج زادت مع زيادة فترة الحضانة: ١٢ ميكرومول (٦٣.٧١٪ ± ٢.١٩٢٪)، ١٦ ميكرومول (٧٤.٥١٪ ± ٤.٥٩٦٪)، و ٢٠ ميكرومول (٧٨.٧٩٥٪ ± ١.٤٣٥٪). تستطيع المادة ١٠ جينجيرول أن تحفز الموت المبرمج للخلايا في الخلايا المحيطة بالبويضة، إلا أنها تثبط وظائف الجين المسؤول عن برمجة مستَقبِل 5- هيدروكسي تريبتامين وتبطل عمل كلا من جلايكوجين سنثايز كاينايز ٣ بيتا والجين المبرمج لـ " أي كي تي - ١ ". الاستنتاجات: تشير نتائج هذه الدراسة إلى أن هناك حاجة لمزيد من الفحص لـ ١٠-جينجيرول كعامل منع للحمل. Abstract: Objectives: Cumulus cells play a crucial role as essential mediators in the maturation of ova. Ginger contains 10-gingerol, which induces apoptosis in colon cancer cells. Based on this hypothesis, this study aimed to determine whether 10-gingerol is able to induce apoptosis in normal cells, namely, cumulus cells. Methods: This study used an in vitro analysis by culturing Cumulus cells in M199 containing 10-gingerol in various concentrations (12, 16, and 20 μM) and later detected early apoptotic activity using an Annexin V-FITC detection kit. Result: The in vitro data revealed that the number of apoptosis cells increased along with the period of incubation as follows: 12 μM (63.71% ± 2.192%); 16 μM (74.51% ± 4.596%); and 20 μM (78.795% ± 1.435%). The substance 10-gingerol induces apoptosis in cumulus cells by inhibiting HTR1A functions and inactivating GSK3B and AKT-1. Conclusions: These findings indicate that further examination is warranted for 10-gingerol as a contraception agent.